Role of cement science in sustainable development proceedings of the international symposium dedicated held at the University of Dundee, Scotland, UK on 3-4 September 2003 - Glasser, F. P.; Dhir, Ravindra K.; Newlands, Moray D.; Csetenyi, Laszlo J. (Thomas Telford, 2003)
Themes covered include: modern cement manufacture; hydration of Portland cement; supplementary cementing materials, activators and inhibitors; performance of Portland cement concrete in the environment; special and non-Portland cements; and exploiting science.
Series of three international symposia to promote the contributions that concrete ... under the umbrella title of Celebrating Concrete, People and Practice"--Preface.
Keywords: Cement -- Environmental aspects -- Congresses.; Sustainable development -- Congresses.; Portland cement -- Environmental aspects -- Congresses.; elektronické knihy; electronic books